Vasculopathy: a possible factor affecting hereditary angioedema - Anna Laura Colia; Alessandra Ranaldi; Rosa Santacroce; Giovanna D'Andrea; Angela Bruna Maffione; Maurizio Margaglione; Maria D'Apolito (Bleeding, Thrombosis and Vascular Biology)
Hereditary angioedema (HAE) is a rare genetic disorder that causes swelling of tissues in the hands, feet, limbs, face, intestinal tract, or airway. The SERPING1 gene, encoding the C1-INH, determines the wide range of clinical symptoms associated with CI-INH deficient HAE. C1-INH regulates enzymes involved in bradykinin production, leading to increased vascular permeability and angioedema. The most prevalent cause of this condition is either a deficiency or dysfunction of C1-INH. A subset of patients exhibits a third form of HAE (nC1-INH-HAE). This clinical subtype, distinguished by the absence of mutations in SERPING1, has a clinical picture similar to C1-INH-HAE but with normal C1-INH level and activity. This review summaries recent progress in genetic characterization of angioedema and discusses future potential for identifying additional genetic abnormalities in HAE. The elucidation of mechanisms leading to HAE could contribute to better understanding of the endothelial cell physiopathology.